Development of River Ecotourism Based on Sustainable Culture in Nagari Manggopoh Agam Regency, West Sumatera - Muhyiatul Fadilah; Suci Fajrina; Delmira Syafrini; Tazkiyah Yuanda; Ghina Salsabila (Fakultas MIPA Universitas Negeri Padang, 2025)
The concept of world tourism has shifted and is moving towards an ecotourism model due to the saturation of tourists visiting artificial tourist attractions. Nagari Manggopoh, located in Agam Regency, West Sumatra Province, has an image as an area rich in ecotourism potential. This is supported by the potential of the Kalulutan River that stretches across Nagari Manggopoh. One of the very unique natural resources found in the waters of the Kalulutan River is Lubuk Larangan. However, Lubuk Larangan, which should be a protection zone for the sustainability of natural resources, has instead become a popular destination for anglers from various regions in Agam Regency. This can result in overfishing. In addition, uncontrolled tourist visits can cause a decrease in the fish population in the river because the activities carried out by these tourists can disrupt the overall aquatic ecosystem. The purpose of this community partnership program is to provide training to the Dasa Wisma Mawar 1 group in an effort to develop sustainable culture-based river ecotourism in Nagari Manggopoh, Agam Regency, West Sumatra Province through a community empowerment approach (community base development). The implementation method used is Oriented-Project Planning (OPP). Based on the results of the study, it can be seen that training on river ecotourism development based on sustainable culture in Nagari Manggopoh is able to increase participants' knowledge about the concept of river ecotourism development and management based on sustainable culture.